The feasibility of applying expert system technology to the performance analysis and tuning of the OS-VS2 MVS operating system - Bryant, D. A.(Deborah Anne) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1988.